Detection of non-homology-containing heteroduplex molecules. - Lichten, M J (1983)
Heteroduplex DNA molecules which contain both the wild-type and mutant sequences of a deletion nonhomology possess a characteristic electrophoretic mobility in agarose and can be readily separated from both the wild-type and deletion-containing parental homoduplex fragments. Because of the partial single stranded character of these deletion-containing heteroduplex molecules, they are selectively bound to nitrocellulose filters, and once bound, can be selectively detected by hybridization with radioactively labeled single-stranded DNA which is homologous to the sequences absent in the deletion mutation.